Application of Human Behavior Patterns on Residential Floors (Case Study: The Jarrdin Apartment, Bandung) - Phoebe Edrica; Hartanto Budiyuwono (Riviera Publishing, 2025)
Changes in urban lifestyles demand vertical housing solutions such as apartments. The Jarrdin Apartment in Bandung City is one example of vertical housing that accommodates thousands of residents within limited space and with significant height differences. This study aims to examine the impact of floor height on residents' physical and psychological comfort, as well as to propose alternative design approaches for human behavioral patterns in vertical spaces. The method used is descriptive qualitative, involving field observations, resident interviews, and literature studies. The results show that floor height influences perceptions of comfort, accessibility, and social interaction, ultimately shaping unique behavioral patterns at each residential level. Alternative design strategies that consider circulation access, natural lighting, social interaction spaces, and perceived safety are crucial for creating more humane vertical dwellings.